Relativization Strategies of Sasak Ngeno Ngene Dialect in Lombok - Nurachman Hanafi; Udin Udin; Eni Djuhaeni; Edy Syahrial (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Relative clauses (RC), in whatever the languages, are essential for investigation especially on how noun phrases as nuclear and oblique relations are workable in Keenan & Comrie’s (1977) Noun Phrase Accessibility Hierarchy. In this paper, Relativization Strategies of Sasak Ngeno-Ngene Dialect in Lombok is presented with the aims are (1) describing the ability of these relations in direct relativization, (2) analyzing the strategies used when indirect relativization occurs, and (3) formulating the right orderings of these relations in the hierarchy. The data on relativization strategies were taken by elicitations, an interview with some informants and documentation of the previous related studies. Then, a careful analysis was made with reference to common linguistic typological approach. The results of this study showed that: (1) gap strategy underlines direct relativization for S (subject) of SVO, O (object) of OVS and OBL of destination, (2) case-coding strategy is preferred by OBL of locative, and (3) passivization strategy is suitable for all indirect relativizations for O (object) of SVO and OBL of benefactive, recipient, and instrumental. The hierarchy of nuclear and oblique relations were formulated: S (SVO) > O (OVS) > OBL (DES > LOC) in direct relativization. Conversely, the hierarchy of O (SVO) > OBL (BEN > RECIP > INST) is shown in indirect relativization.